Management and Valuation of Heritage Assets A Comparative Analysis Between Italy and USA - Landriani, Loris; Pozzoli, Matteo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
The valuation of Heritage Assets (HA), which are a vital resource for the non-profit public or private organizations operating in the heritage sector is on the one hand sometimes difficult to do, and on the other, can be excessively costly with respect to the correlated disclosure benefits. The growing application of the (full or modified) accrual basis of accounting in the public and non-profit sectors has extended and reanimated this issue. This book applies the comparative method, in order to provide new information on the analyzed subject. Specifically, after having investigated the different theoretical and technical proposals, it compares the reporting behavior of significant cases of Italian and American public and private organizations, coming from different cultural and management approaches. Proposing a link between the managerial and reporting issues of the organizations involved in the management and maintenance of heritage assets, this book is crucial in the task to optimize the performance of organizations in this sector.
Introduction -- The Definition of Heritage Assets -- Hypothesis and Research Methodology -- The System of Cultural Heritage in Italy -- The System of Cultural Heritage in the United States -- Accounting for Heritage Assets -- Conclusions.
Keywords: Accounting; Bookkeeping .; Business ethics; Public administration; Accounting/Auditing.; Business Ethics; Public Administration